Let the beta and the zeta function be defined as usual:

\begin{align} & \beta(s) & = & \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^s} & = & 1-\frac{1}{3^s}+\frac{1}{5^s}\dots +\frac{(-1)^n}{(2n+1)^s}+\dots \\ & \zeta(s) & = & \sum_{n=1}^\infty \frac{1}{n^s} &= & 1+\frac{1}{2^s}+\frac{1}{3^s}+\dots +\frac{1}{n^s}+\dots \end{align}


Is there a closed form for $$\sum_{n=1}^\infty \frac{1-\beta(n)}{n}$$


I was hunting for some analogues to the zeta function while reading this. In the post we can find

$$ \begin{align} & \sum_{n=2}^\infty \zeta(n)-1 & = & 1 \\ & \sum_{n=2}^\infty \zeta(2n)-1 & = & 3/4 \\ & \sum_{n=2}^\infty \frac{\zeta(n)-1}{n} & = & 1-\gamma \end{align} $$

Where $\gamma$ is the Euler-Mascheroni constant

So I found analogues for the first two but I can't quite see if this is possible for the third. I found using the techniques of the accepted answer in the link above (and it can also be found here):

$$\sum_{n=1}^\infty 1-\beta(n)= \ln(\sqrt2) $$ and $$ \sum_{n=1}^\infty 1-\beta(2n)= \ln(\sqrt2)-\frac{1}{4} $$

Possibly a red herring but hopefully not:

$$\sum_{n=1}^\infty \frac{1-\beta(n)}{n} \approx \ln (L/2)=\ln\bigg( \int_0^1 \frac{dx}{\sqrt{1-x^4}} \bigg) $$ These match up for at least the first 100 decimal places. Where $L=2.62205755429 \dots $ is the Lemniscate constant. If these two are equal my question becomes: What is the connection between the Lemniscate constant and the $\beta$ function?

  • $\begingroup$ This computation regarding the Lemniscate constant was done by using wolfram alpha: N[1 - DirichletBeta[1] + Sum[(1 - DirichletBeta[n])/n, {n, 2,2000}], 100]. and I compared it to this. $\endgroup$ – Mason Apr 23 '20 at 1:11

First of all : $$ \prod_{k=1}^{n}{\left(1+\frac{1}{4p}\right)}\prod_{k=0}^{n}{\left(1-\frac{1}{4p+3}\right)}=\frac{4\Gamma\left(\frac{7}{4}\right)\Gamma\left(n+\frac{5}{4}\right)\Gamma\left(n+\frac{3}{2}\right)}{3\sqrt{\pi}\Gamma\left(\frac{5}{4}\right)\Gamma\left(n+1\right)\Gamma\left(n+\frac{7}{4}\right)}\underset{n\to +\infty}{\longrightarrow}\frac{4\Gamma\left(\frac{7}{4}\right)}{3\sqrt{\pi}\Gamma\left(\frac{5}{4}\right)} $$

Let $ n $ be a positive integer, we have the following : \begin{aligned}\sum_{p=1}^{2n+1}{\left(-1\right)^{p}\ln{\left(1+\frac{1}{2p}\right)}}&=\sum_{k=1}^{n}{\ln{\left(1+\frac{1}{4p}\right)}}-\sum_{k=0}^{n}{\ln{\left(1+\frac{1}{4p+2}\right)}}\\&=\ln{\left(\prod_{k=1}^{n}{\left(1+\frac{1}{4p}\right)}\prod_{k=0}^{n}{\left(1-\frac{1}{4p+3}\right)}\right)} \end{aligned}

Thus, $ \sum\limits_{p\geq 0}{\left(-1\right)^{p}\ln{\left(1+\frac{1}{2p}\right)}} $ converges, and its sum values $ \ln{\left(\frac{4\Gamma\left(\frac{7}{4}\right)}{3\sqrt{\pi}\Gamma\left(\frac{5}{4}\right)}\right)}\cdot $

Now, since $ \sum\limits_{n\geq 1}{\frac{\left(-1\right)^{n-1}}{\left(2n+1\right)^{s}}} $ converges absolutly, for any $ s>1 $, we can prove that the family $ \left(\frac{\left(-1\right)^{p-1}}{n\left(2p+1\right)^{n}}\right)_{\left(p,n\right)\in\mathbb{N}^{*}\times\mathbb{N}^{*}\setminus\left\lbrace 1\right\rbrace} $ is summable, and hence, thanks to Fubini's theorem, we can write the following : \begin{aligned}\sum_{n=2}^{+\infty}{\frac{1-\beta\left(n\right)}{n}}=\sum_{n=2}^{+\infty}{\sum_{p=1}^{+\infty}{\frac{\left(-1\right)^{p-1}}{n\left(2p+1\right)^{n}}}}=\sum_{p=1}^{+\infty}{\sum_{n=2}^{+\infty}{\frac{\left(-1\right)^{p-1}}{n\left(2p+1\right)^{n}}}}\end{aligned}

After switching the summations, adding the first term of the sum, recognising logarithm's series expansion, we get that : $$ \sum_{n=1}^{+\infty}{\frac{1-\beta\left(n\right)}{n}}=\sum_{p=1}^{+\infty}{\left(-1\right)^{p-1}\ln{\left(1+\frac{1}{2p}\right)}}=\ln{\left(\frac{3\sqrt{\pi}\Gamma\left(\frac{5}{4}\right)}{4\Gamma\left(\frac{7}{4}\right)}\right)} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.